Ceramics: an update - Cascante Calderón, Marcelo (2019)
The dental ceramics used to restore and replace lost tooth tissue or the teeth have undergone a huge transformation since the first porcelains appeared several decades ago. With the feldspathic teeth, crowns and bridges could be made but, they needed a metal support so that they did not suffer fractures with the masticatory efforts, and therefore they did not have a vital appearance. Today, many other ceramics with different and improved mechanical and optical characteristics have appeared, which has allowed dentists to offer artificial teeth to their patients for the first time with surprising naturalness. Objective: Describe the current classification, mechanical and optical characteristics, as well as the microstructure and clinical uses of the different dental ceramics used today. Materials and methods: Review about the literature on the subject, in three of the most important internet search engines (Pubmed, Cochrane, Web of Science). Limiting your search to articles in English and published in the journals of research of dental materials with qualification Q1 and Q2. Results: 69 articles published between 1975 and 2019 were reviewed, which provided an interesting source of information that allowed the development of knowledge about classification, microstructure, mechanical and optical properties, clinical uses and method of processing ceramics. Conclusions: Currently, dentists have available a wide variety of ceramic materials with different compositions and unique characteristics that are necessary to know when choosing the specific ceramic for each patient need.